Detecting Deception within Small Groups: A Literature Review - Vernham, Zarah; Granhag, Pär-Anders; Mac Giolla, Erik (Frontiers in Psychology, 2016)
Investigators often have multiple suspects to interview in order to determine whether they are guilty or innocent of a crime. Nevertheless, co-offending has been significantly neglected within the deception detection literature. The current review is the first of its kind to discuss co-offending and the importance of examining the detection of deception within groups. Groups of suspects can be interviewed separately (individual interviewing) or simultaneously (collective interviewing) and these differing interviewing styles are assessed throughout the review. The review emphasises the differences between lone individuals and groups. It focuses on the theoretical implications of group deceit and the reasons why groups need to be understood in terms of investigative interviewing and deception detection if all types of crime-related incidents are to be recognised and dealt with appropriately. Group strategies, consistency within- and between-statements, joint memory, and group dynamics are referred to throughout the review and the importance of developing interview protocols specifically for groups is discussed. The review concludes by identifying the gaps in the literature and suggesting ideas for future research, highlighting that more research is required if we are to obtain a true understanding of the deception occurring within groups and how best to detect it.